Structural aspects of dormancy in quinoa (Chenopodium quinoa): Importance and possible action mechanisms of the seed coat - Ceccato, Diana Valeria (2015)
Two possible sources of resistance to pre-harvest sprouting were evaluated in quinoa. They showed dormancy at harvest and significant variations in dormancy level in response to environmental conditions experienced during seed development. The aims of this work were to evaluate the importance of seed coats in the regulation of dormancy in this species, to investigate possible mechanisms of action and to assess association of seed coat properties with changes in dormancy level caused by the environment. Accessions Chadmo and 2-Want were grown under field conditions on different sowing dates during 2 years. Seed coats were manipulated and seed germination was evaluated at different temperatures. Seed coat perforation before incubation led to faster dormancy loss in both accessions. This effect decreased with delayed sowing date, and seeds expressed a level of dormancy not imposed by coats. This suggests the presence of embryo dormancy in the genus Chenopodium . Seeds of the accession 2-Want had a significantly thinner seed coat at later sowing dates, associated with a decreasing coat-imposed dormancy, but this pattern was not detected in Chadmo. The seed coat acts as a barrier to the release of endogenous abscisic acid (ABA) in quinoa, suggested by the increase in germination and a higher amount of ABA leached from perforated seeds. ABA is able to leach from seeds with an intact seed coat, suggesting that differences in seed coat thickness may allow the leakage of different amounts of ABA. This mechanism may contribute to the observed differences in dormancy level, either between sowing dates or between accessions.